Fruit quality of bilberry (Vaccinium myrtillus L.) in boreal forests: Effects of forest stand, understorey, and soil characteristics - Manninen, Outi H.; Martz, Françoise; Sorvari, Jouni; Merilä, Päivi (Elsevier, 2025)
The bilberry (Vaccinium myrtillus L.) is an essential wild berry species in Northern Europe, valued for its sweet taste and chemical compounds. The growing environment, particularly the light and temperature conditions, affects the quality of bilberry fruits. However, studies of their quality in boreal forests are scarce. We analyzed the total phenolics, anthocyanins (ACN), flavonols, iridoids and sugars of bilberry fruits collected from 28 forests in central Finland, to identify the characteristics of forest structure, understorey, and soil that best indicate fruit quality. Forest structure was characterized by canopy cover (leaf area index, LAI), mean age and dominant tree species. The mean (± SD) values of the total phenolics, ACNs, iridoids and sugars in bilberry fruits were 88.7 ± 14.2, 78.9 ± 13.4, 0.52 ± 0.11 and 339.1 ± 44.6 mg g−1 d.w., respectively. Based on linear mixed models, forest structure was the strongest predictor of high phenolics and ACNs, while soil organic layer best explained sugar concentrations. Moreover, daily minimum temperatures correlated with higher sugar levels. A significant interaction between the dominant tree species and LAI indicated that light availability increased phenolic content in bilberry fruits in spruce dominated forests. When comparing different forest stand types, bilberry fruits from drained peatland pine forests exhibited the highest levels of ACNs. High ACNs were associated with high graminoid abundance in the understorey. These findings could direct the harvesting of high-quality bilberry fruits and reveal the intricate relationship between bilberry fruit quality, forest stands and site characteristics in natural ecosystems.
Keywords: anthocyanins; boreal forest; exposure to light; phenolics; temperature; flavonols